Social Interaction Skills and Learning Process of Children with Special Needs with Multiple Specialties - Oktafiolita, Anggraini; Rizkita, Ika Wahyu; Sartinah, Endang Pudjiastuti; Murtadlo, Murtadlo (PT ARRUS Intelektual Indonesia, 2024)
This article examines the social interaction skills and learning process of children with special needs with multiple disabilities, including autism, intellectual disabilities, and other developmental disorders. Social interaction is identified as a crucial factor affecting children's academic and emotional development. This study explores the various challenges faced by children in building social relationships and communication with their environment. In addition, this article presents effective learning strategies, such as individual approaches and inclusive environments, to improve social skills. The findings suggest that with proper support, children with special needs can develop better interaction skills, which contribute to improving their quality of life. This article aims to provide insights for educators, parents, and practitioners in designing educational programs that are more responsive to children's needs.